Beyond remedicalisation: a community-led PrEP demonstration project among sex workers in India. Issue 9 (1st September 2021) - Lazarus, Lisa; Reza-Paul, Sushena; Rahman, Syed Hafeez Ur; Ramaiah, Manjula; Venugopal, M.S.; Venukumar, K.T.; Moses, Stephen; Becker, Marissa; Lorway, Robert
Abstract: Global health policy-makers have called for demonstration projects to better understand pre-exposure prophylaxis' (PrEP) effectiveness across geographies and populations. Ashodaya, a sex worker collective, initiated a PrEP project in Mysore, India. We conducted a project ethnography to explore the role that community participation played within the project. Although the project proved immensely successful in terms of retention and adherence, to explain these findings we point towards Ashodaya's history of collectivisation around sexual health—a history of community action that has given rise to new spaces of belonging and accumulated knowledges that became instrumental in the formulation of strategies to confront anticipated challenges during the project. These strategies included: (1) the participation of community leaders as the first participants to take PrEP, followed by the sharing of their experiences through testimonials to their peers; (2) the endorsement of PrEP among community leaders living with HIV, to avoid social divisions around HIV status; and (3) ongoing community-level support from outreach workers that went beyond administering PrEP to address the various needs of the community. These community-led approaches demonstrate that communities hold key insights into the delivery of clinically-oriented interventions, suggesting the vital role they continue to play in planning and implementing new prevention technologies.